Neocosmocercella fisherae n. sp. (Nematoda: Cosmocercidae), a parasite of the large intestine of Phyllomedusa bicolor (Boddaert) (Anura: Phyllomedusidae) from the Brazilian Amazon - dos Santos, Ana Nunes (2018)
Neocosmocercella fisherae n. sp. is the first nematode species found parasitising Phyllomedusa bicolor from the Brazilian Amazon Region. The new species has a triangular oral opening, with bi-lobed lips, and is distinguished from N. bakeri (triangular oral opening with simple lips), and from N. paraguayensis (hexagonal oral opening with bi-lobed lips). Additionally, the new species has ciliated cephalic papillae, which are absent in the other species of the genus. The reduced uterine sac and the presence of a single egg in the uterus in females are the main morphological characters that differentiate the new species from its congeners N. bakeri (8–10 eggs) and N. paraguayensis (10 eggs, based on the allotype). Additionally, the new species differs from the other two species of the genus by morphometric characters such as the size of spicules and gubernaculum in males and the vagina in females. Until now, phyllomedusid anurans are the only known hosts for the nematodes of this genus. The present work describes the third species of the genus and the first species of nematode parasitising P. bicolor.